Prevalence of Phytochemical and Pharmacological Properties; Furthermore, a Miraculous Healing Plant in the Contemporary Time, Annona reticulata - Basappa, Kavya Shree; Raghava, Sri; Umesha, Sharanaiah (Pharmacognosy Communications)
As old as humanity itself, medicinal plants have been used to treat illnesses. The use of medicinal herbs has not decreased despite any scientific advancement. The history of the relationship between mankind and the search for drugs predates now. There used to be a dearth of information regarding therapeutic plants, but his search never came to an end. Man's long-running battles with disease prompted him to hunt for pharmaceuticals in the barks, seeds, fruit bodies, and other sections of plants, which led to the understanding of employing therapeutic plants. Modern science has recognized its importance, accepted the active action, and added a variety of plant-based medications that have been used for millennia by ancient cultures to modern pharmacotherapy. One such plant that may be proudly included in this group is Annona reticulata. Phytochemicals and other plant-derived molecules are used in a variety of products, including medicines, cosmetics, food supplements, and other goods. A. reticulata serves as a source for both commercial and therapeutic products. There are many different therapeutic benefits it can have, such as anthelmintic, analgesic, anti-inflammatory, antipyretic, wound-healing, anti-cancer, and cytotoxicity effects. A wide variety of phytochemicals, including tannins, alkaloids, phenols, glycosides, flavonoids, and steroids, are widely distributed in it. The purpose of this review is to evaluate the potential value of the A. reticulata plant in the creation of new plant-based medications. The healing power of medicinal plants has emerged in the modern era as a mirror of light.
Keywords: Medicinal Plants; Annona reticulata; Phytochemicals; Healing power; Plant based medications.